Atratividade de nematoides entomopatogênicos na presença de plantas para diversificação vegetal na cultura do tomateiro - Ramos, Dalilia Ambrosia (2023)
Entomopathogenic nematodes (NEPs) are beneficial nematodes from an agronomic point of view, as they parasitize and kill insect pests through the release of their symbiotic bacteria. As they have a free-living phase in the soil, they can benefit from an environment that provides adequate humidity and temperatures. Cover crops, in turn, improve the physical conditions of the soil, and many species release volatile compounds that act as attractants for biological control agents. The aim of this study was to evaluate alternative methods of controlling B. tabaci by testing the attractiveness of cover crops clove (Tagetes spp.), marigold (Calendula oficinalis L.), coriander (Coriandrum sativum L.) and buckwheat (Fagropyrum esculetum Moench) and three tomato genotypes (Lycopersicon pennelli, T10R2#3 and cv. Santa Clara) on isolates of the entomopathogenic nematode (NEP) Heterorhabditis amazonensis MC01. The completely randomized design (DIC) and the Scott-Knott test (p ≤ 0.05) were used for all tests. When assessing the attraction of cover crops to infective juveniles (IJ) (350,000 IJ per repetition), all cover crops attracted NEP, with buckwheat being the most attractive. In the test of the attractiveness of buckwheat and the three tomato genotypes to NEP (30,000 NEP per repetition), the highest averages were obtained by the genotypes T10R2R3 and L. pennelli. In the IJ targeting test (30,000 IJ per repetition) in relation to the Santa Clara and T10R2#3 cv. genotypes, free or infested by B. tabaci, no statistical differences were observed between the treatments. In the evaluation of the presence of B. tabaci in the cv. Santa Clara and T10R2#3, grown in substrate free of or infested by IJ (30,000 IJ per repetition), the T10R2#3 genotype was less attractive to B. tabaci, regardless of whether or not its substrate was infested by NEP. Finally, the behavior of IJ (50,000 IJ per repetition) was evaluated in relation to tomato genotypes alone or in intercropping with buckwheat. In tomato plants free from whitefly infestation, all genotypes were more attractive to NEP when intercropped with buckwheat, with the exception of T10R2#3. In the test with tomato plants infested by B. tabaci, the plants intercropped with buckwheat were the most attractive to NEP, regardless of genotype. It can be concluded that buckwheat is attractive to NEPs and can be intercropped with tomato plants in order to promote the presence of NEPs in the area.